PELUANG DAN TANTANGAN EFISIENSI MEDIA DALAM PROGRAM PENJAMINAN MUTU TK NEGERI 3 KAWAY XVI ACEH BARAT - Rahmattullah Rahmattullah; Musdiani; Astuti (LPPM Universitas Cipta Mandiri, 2026)
Quality assurance in early childhood education requires effective resource management, including theutilization of learning media. Media efficiency is an important strategy for improving learning qualitythrough the use of appropriate, economical, and developmentally suitable learning resources. This studyaims to analyze the opportunities and challenges of media efficiency in the quality assurance programat State Kindergarten 3 Kaway XVI District, West Aceh Regency. This study employed a qualitativedescriptive method using Strengths, Weaknesses, Opportunities, Threats analysis. Data were collectedthrough observation, interviews, and documentation involving the principal and teachers. The resultsshowed that the school has strengths in teachers’ creativity in utilizing environmental-based media, theavailability of local learning resources, and commitment to improving learning quality. Severalweaknesses were identified, including limited facilities, funding, and technological media developmentskills. Opportunities for developing media efficiency include educational policy support, localenvironmental potential, and collaboration with various stakeholders. The challenges include increasingdemands for digital learning and limited resources. Based on the analysis, the development strategy formedia efficiency focuses on optimizing local potential, improving teacher competence, and graduallyintegrating technology to support quality improvement in early childhood education.